2013
DOI: 10.1007/s11121-013-0420-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning and Depressive Symptoms Among HIV-Positive Persons Receiving Care and Treatment in Kenya, Namibia, and Tanzania

Abstract: In sub-Saharan Africa, the prevalence of depressive symptoms among people living with HIV (PLHIV) is considerably greater than that among members of the general population. It is particularly important to treat depressive symptoms among PLHIV because they have been associated with poorer HIV care-related outcomes. This study describes overall psychosocial functioning and factors associated with depressive symptoms among PLHIVattending HIV care and treatment clinics in Kenya, Namibia, and Tanzania. Eighteen HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 54 publications
(78 reference statements)
5
71
0
Order By: Relevance
“…The greater social acceptance of females than males may be due to the entrance of more females into universities and high levels of education, knowledge, and social relations in the last decades in Iran. In contrast, additional studies conducted in Tanzania, Namibia and Kenya indicated that higher levels of depressive symptoms were associated with being female (12). Another study indicated that males experienced greater acceptance than females (13).…”
Section: Discussionmentioning
confidence: 90%
“…The greater social acceptance of females than males may be due to the entrance of more females into universities and high levels of education, knowledge, and social relations in the last decades in Iran. In contrast, additional studies conducted in Tanzania, Namibia and Kenya indicated that higher levels of depressive symptoms were associated with being female (12). Another study indicated that males experienced greater acceptance than females (13).…”
Section: Discussionmentioning
confidence: 90%
“…Further, adolescents with HIV may experience higher rates of depression, anxiety, and traumatic experiences than their uninfected peers (T. Betancourt et al, 2014; Kamau, Kuria, Mathai, Atwoli, & Kangethe, 2012; Seth et al, 2014). Despite these statistics, mental health research and services are scarce for HIV-positive youth, especially in low-resource settings (Klasen & Crombag, 2012; Patel, Flisher, Nikapota, & Malhotra, 2008; Thapar, Collishaw, Pine, & Thapar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent evidence suggests that psychosocial factors and depression are interrelated. Studies conducted in sub-Saharan Africa have identified associations between depressive symptoms and both low levels of social support [15] and high levels of HIV-related stigma [16, 17], and recent research conducted among HIV-infected men and women in South Africa has reported that both HIV-related stigma and social support are independently associated with depression [18]. However, the interrelationships among these constructs are poorly understood, and most previous research has not explored the potentially moderating effect of these factors on the relationships between other factors and depression.…”
Section: Introductionmentioning
confidence: 99%